Philosophical investigations - Wittgenstein, Ludwig 1889-1951; Anscombe, G.E.M. (Oxford Basil Blackwell, 1958)
Incorporating significant editorial changes from earlier editions, the fourth edition of Ludwig Wittgenstein's Philosophical Investigations is the definitive en face German-English version of the most important work of 20th-century philosophyThe extensively revised English translation incorporates many hundreds of changes to Anscombes original translationFootnoted remarks in the earlier editions have now been relocated in the textWhat was previously referred to as Part 2 is now republished as Philosophy of Psychology A Fragment, and all the remarks in it are numbered for ease of referenceNew detailed editorial endnotes explain decisions of translators and identify references and allusions in Wittgenstein's original textNow features new essays on the history of the Philosophical Investigations, and the problems of translating Wittgensteins text